Demokrasi dan Penegakan Hukum dalam Wawasan Al-Qur’an - Ritonga, Muhammad Soleh (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2021)
Islam is a religion that regulates people's lives. This includes democracy and law enforcement. In democracy there are several views of Muslim experts, some accept but on the condition that the power is not absolute in the hands of the people, and there are also those who reject it altogether. In the ulama democracy accepted in Islam is deliberation and consensus in matters that are in accordance with religious rules. In Islamic democracy, it is very radicalism. This can be seen from the views of some scholars of Tafsir regarding Surah Al-Baqarah verse 143 that Islam is not exceeding the limit. Meanwhile, good law enforcement can be created because of a well-executed democracy. In Islam, law enforcement is a profession that is not easy. There are criteria and ethics for judges as law enforcers so that the law can produce a fair law. In the enforcement of the law must glorify God's commandments and have a sense of compassion or concern and a deep sense of justice that is shown. Democracy and law enforcement in the perspective of the Qur'an there are ethics that must be done, so that democracy and law enforcement cannot be separated from religion as secular views separate religion from worldly problems. Religion with the guidance of the holy book Al-Qur'an plays an important role in guiding democracy and good law enforcement.